Investigation on the effect of Mn substitution on the structural, electrical and ferroelectric characteristics of Bi0.5Na0.5TiO3 ceramic. (November 2019) - Pradhani, Neeha; Mahapatra, P.K.; Choudhary, R.N.P.; Jena, A.K.; Mohanty, J.
Graphical abstract: Highlights: Rietveld refinement confirms the compounds crystallize with rhombohedral (R3c) symmetry. A small tangent loss with high dielectric constant and improved ferroelectric characteristics is achieved. Resolution of loss tangent to grain, grain boundary relaxation, and conductivity. Abstract: The perovskite compounds, Bi0.5 Na0.5 Ti1- x Mn x O3 ( x = 0, 0.05, 0.10, 0.15), were synthesized by a mixed oxide technique. The compound formation was confirmed from the energy dispersive X-ray and Fourier transform infrared spectra. The field emission scanning electron micrographs exhibit a uniform distribution of grains with larger grains for the compound with higher Mn content. The high dielectric constant, low dielectric tangent loss, higher remnant polarization and lower coercive field of the compound ( x = 0.05) make it suitable for device applications. The value of the static and infinite frequency dielectric constant for Bi0.5 Na0.5 Ti0.95 Mn0.05 O3 is obtained from Nyquist and Cole-Cole plots. The tangent loss has been resolved to identify the Debye type contribution of grain and grain boundary and the contribution of DC conductivity. Analysis of the temperature dependence of AC conductivity data shows the activation of defect/vacancy beyond 280 °C and flip flop between multivalent Mn ions in the studied temperature range.